Two new species of Lerista Bell, 1833 (Reptilia: Scincidae) from north Queensland populations formerly assigned to Lerista storri Greer, McDonald and Lawrie, 1983 - Amey, Andrew P.; Couper, Patrick J.; Wilmer, Jessica Worthington (Zootaxa, 2019)
Ongoing surveys for skinks of the genus Lerista in north Queensland have resulted in the collection of voucher specimens from two populations formerly assigned to Lerista storri Greer, McDonald & Lawrie, 1983 that are geographically isolated from the type population and show a degree of morphological variation differing from the type population. Analysis of recently collected material has confirmed both populations are specifically distinct to the type population, with one being more closely related to Lerista ameles Greer, 1979, another little known, north Queensland species. Consequently, these populations are described as Lerista alia sp. nov. and Lerista parameles sp. nov. The morphological diversity of L. storri is thereby restricted, necessitating a redescription. The conservation status of all these taxa is discussed.